Improving Students’ Science Problem Solving Ability through the Implementation of Problem Based Learning Models Assisted by Animation Media - Salim, Faisal; Purwanto, Agung; Lestari, Ika (Universitas Pendidikan Ganesha, 2024)
The low ability of students to solve science problems is caused by the lack of effectiveness in the use of learning models and media. This study aims to analyze the effect of problem-based learning models assisted by animation media on the ability to solve science problems for grade IV elementary school students. The research method used was an experiment using a posttest-only control design. The samples taken using the simple cluster random sampling technique amounted to 30 students in the experimental group and 30 students in the control group. Data analysis techniques used includes descriptive statistics and inferential statistics by testing hypotheses using t-tests. The results showed that the average score in the experimental group was 82.4, while in the control group was 59.1. The results of the hypothesis test showed that the value of Sig. (2-tailed) was 0.000 < 0.05 or less than (α=0.05), indicating a significant difference in science problem-solving ability between students in the experimental group and the control group. Based on the results of the study, it can be concluded that the problem-based learning model assisted by animation media has a significant influence on the science problem-solving ability of grade IV elementary school students. With the results of this research, it is hoped that teachers can integrate problem-based learning models and animation media in the learning process to improve students' science problem-solving abilities in elementary schools.